Advances in drug discovery of new antitubercular multidrug-resistant compounds - Fernandes, Guilherme Felipe dos Santos [UNESP]; Chin, Chung Man [UNESP]; Dos Santos, Jean Leandro [UNESP] (MDPI, 2017)
Tuberculosis (TB), a disease caused mainly by the Mycobacterium tuberculosis (Mtb), is according to the World Health Organization (WHO) the infectious disease responsible for the highest number of deaths worldwide. The increased number of multidrug-resistant (MDR-TB) and extensively drug-resistant (XDR-TB) strains, and the ineffectiveness of the current treatment against latent tuberculosis are challenges to be overcome in the coming years. The scenario of drug discovery becomes alarming when it is considered that the number of new drugs does not increase proportionally to the emergence of drug resistance. In this review, we will demonstrate the current advances in antitubercular drug discovery, focusing on the research of compounds with potent antituberculosis activity against MDR-TB strains. Herein, active compounds against MDR-TB with minimum inhibitory concentrations (MICs) less than 11 µM and low toxicity published in the last 4 years in the databases PubMed, Web of Science and Scopus will be presented and discussed.
Keywords: Antitubercular compounds; Drug discovery; Multidrug-resistant tuberculosis; Tuberculosis